Rapid And Sensitive Colorimetric Detection Of Caffeine For Forensic Applications - Gupta, Dr. Geeta; Rawal, Komal (Metallurgical and Materials Engineering, 2025)
Caffeine, a methylxanthine alkaloid, is a naturally occurring stimulant found in plants such as Coffea arabica (coffee), Camellia sinensis (tea), and Theobroma cacao (cocoa). It is widely present in beverages, pharmaceuticals, and dietary supplements. While caffeine is generally considered safe in moderate doses, excessive consumption or misuse can lead to toxicity, making its detection crucial in forensic investigations. Cases involving drug adulteration, overdose, poisoning, and forensic toxicology often require rapid and reliable methods for caffeine identification. However, conventional analytical techniques like chromatography and spectrophotometry, though highly accurate, require sophisticated instruments and time-consuming sample preparation, limiting their use in field applications. This study introduces a novel colorimetric method for caffeine detection using iodine and methanol, which has not been previously reported in forensic science. When iodine is dissolved in methanol, and caffeine is introduced, a distinct color change occurs due to the formation of a charge-transfer complex. Caffeine donates electrons to iodine resulting in a visually detectable shift in color. This test is rapid, cost-effective, and highly sensitive, capable of detecting trace amounts of caffeine, making it ideal for preliminary forensic screening. The method was systematically evaluated across a range of sample dilutions to establish its effective detection limits. A distinct and consistent colorimetric response was observed within the concentration range of 0.1 mg/mL to 2 mg/mL, ensuring reliable visual detection even at lower caffeine levels. Below 0.1 mg/mL, the color change became too faint for clear identification, while concentrations exceeding 2 mg/mL did not produce any significant increase in visual intensity. Due to its simplicity, this technique is highly suitable for on-site forensic applications such as drug seizure inspections, toxicological evaluations, and detection of beverage adulteration. It offers a rapid, qualitative indication of caffeine presence enabling quick preliminary assessments. However, because other electron-donating compounds may interfere with the test, confirmatory analysis through more advanced techniques like chromatography or spectrophotometry is still essential for precise identification and quantification. This study thoroughly investigates the underlying reaction mechanism, sensitivity range, dilution effects, and potential interferences associated with the proposed colorimetric method. With optimization, it holds promise as a valuable initial screening tool in various forensic and toxicological scenarios.